The first decade of biomedical engineering degree program at the University of Malaya: experiences and achievements - Kadri, Nahrizul Adib; Raha, M.G.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar (2008)
The Department of Biomedical Engineering, at the Faculty of Engineering, University of Malaya was established in the 1997/1998 academic session with an intake of 20 students and five academic staff. The Department has undergone numerous changes in the structure of its degree programme, with each one of them recognised and fully accredited by the Engineering Accreditation Council and Ministry of Higher Education. The Department has played an active role at national and global levels, in the areas of biomedical engineering education and research collaboration. Several initiatives have been planned to ensure the Department stays at the forefront of disseminating biomedical engineering innovations in Malaysia.